ANALISIS PERILAKU KONSUMEN GENERASI MILENIAL DALAM BERBELANJA ONLINE - Lesmana, Teguh (Fakultas Ekonomi dan Bisnis, 2023)
The advancement of information and communication technology has transformed the way consumers shop with the presence of online buying and selling platforms. One significant group contributing to this trend is the millennial generation. This study aims to analyze the consumer behavior of the millennial generation in the context of online shopping. Through this research, we intend to identify the factors influencing purchasing decisions, product preferences, and potential barriers faced by millennial consumers when shopping online. The research methodology uses qualitative involves surveys and data analysis from millennial respondents participating in online shopping activities. The outcomes of this study are expected to provide deeper insights into the consumer behavior of the millennial generation in the e-commerce environment and guide the development of more effective marketing strategies.Key words: Technological Advancements, Online Shopping, Millennial Generation